An open letter to Mr. Secretary general of the united nations to propose setting up global standards for conquering growth limits of capitalism - JinHyo Joseph Yun; Philip Cooke; Fumio Kodama; Fred Phillips; Anil K. Gupta; Francisco Javier Carrillo Gamboa; Venni Krishna; Keun Lee; KongRae Lee; Ulrich Witt; Natalja Lace; SangOk Choi; et al. (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
We propose an international economic agenda to overcome the growth limits of capitalism that can be supported by the United Nations. Sustainable Environment based global goals should be added to sustainable economy. For this, we propose dynamic balance between three sub-economies such as open innovation, closed innovation, and social innovation sub-economy. For this, we propose to set up a UN community and a long range plan.
Keywords: 650; The growth limit of capitalism; UN; Open innovation